New species of Pavlovophyceae (Haptophyta) and revision of the genera Exanthemachrysis, Rebecca and Pavlova - Véron, Benoît; Rougier, Etienne; Taylor, Anthony; Goux, Didier (European Journal of Taxonomy, 2023)
The justification of the 4 genera that currently compose the class Pavlovophyceae is based on a low number of species and a relative paucity of available, traceable and referenced cultures. Previous integrative phylogeny work revealed strains that can refine and strengthen our knowledge of the genera in the class. The application of multiple light and electron microscopy techniques allowed us to prioritize the cytomorphological characters (pyrenoid, thylakoid, stigma, knob-scales, life stage / life cycle) used for the taxonomy of these algae and to describe two new species: Exanthemachrysis fresneliae Véron sp. nov. and Rebecca billardiae Véron sp. nov. Consequently, revisions of the two genera Exanthemachrysis Lepailleur emend. Véron and Rebecca Green emend. Véron were made. In addition, the genus Pavlova Butcher emend Véron is revised in the light of these characters. Particular emphasis is placed on the life stages and habitat of the species.